Intransitive competition is common across five major taxonomic groups and is driven by productivity, competitive rank and functional traits. (16th April 2018) - Soliveres, Santiago; Lehmann, Anika; Boch, Steffen; Altermatt, Florian; Carrara, Francesco; Crowther, Thomas W.; Delgado‐Baquerizo, Manuel; Kempel, Anne; Maynard, Daniel S.; Rillig, Matthias C.; Singh, Brajesh K.; Trivedi, Pankaj; et al.
Abstract: Competition can be fully hierarchical or intransitive, and this degree of hierarchy is driven by multiple factors, including environmental conditions, the functional traits of the species involved or the topology of competition networks. Studies simultaneously analysing these drivers of competition hierarchy are rare. Additionally, organisms compete either directly or via interference competition for resources or space, within a local neighbourhood or across the habitat. Therefore, the drivers of competition could change accordingly and depend on the taxa studied. We performed the first multi‐taxon study on pairwise competition across major taxonomic groups, including experiments with vascular plants, mosses, saprobic fungi, aquatic protists and soil bacteria. We evaluated how general is competition intransitivity from the pairwise competition matrix including all species and also for each possible three‐species combination (triplets). We then examined which species were likely to engage in competitive loops and the effects of environmental conditions, competitive rank and functional traits on intransitive competition. We found some degree of competition intransitivity in all taxa studied, with 38% to 5% of triplets being intransitive. Variance in competitive rank between species and more fertile conditions strongly reduced intransitivity, with triplets composed of species differing widely in their competitive ranks much less likely to be intransitive. Including functional traits of the species involved more than doubled the variation explained compared to models including competitive rank only. Both trait means and variance within triplets affected the odds of them being intransitive. However, the traits responsible and the direction of trait effects varied widely between taxa, suggesting that traits can have a wide variety of effects on competition. Synthesis . We evaluated the drivers of competition across multiple taxa and showed that productivity and competitive rank are fundamental drivers of intransitivity. We also showed that not only the functional traits of each species, but also those of the accompanying species, determine competition intransitivity. Intransitive competition is common across multiple taxa but can dampen under fertile conditions or for those species with large variance in their competitive abilities. This provides a first step towards predicting the prevalence of intransitive competition in natural communities. Abstract : We evaluated the drivers of competition across multiple taxa and showed that productivity and competitive rank are fundamental drivers of intransitivity. We also showed that not only the functional traits of each species, but also those of the accompanying species, determine competition intransitivity. Intransitive competition is common across multiple taxa but can dampen under fertile conditions or for those species with large variance in their competitive abilities. This provides a first step towards predicting the prevalence of intransitive competition in natural communities.